Effect of mutations in capsid shell protein on the assembly of BmCPV virus-like particles. (17th March 2021) - Ren, Feifei; Swevers, Luc; Lu, Qiuyuan; Zhao, Yongchao; Yan, Jiming; Li, Haiyun; Sun, Jingchen
Abstract : Bombyx mori cytoplasmic polyhedrosis virus (BmCPV) is a typical single-layer capsid dsRNA virus belonging to the genus Cypovirus in the family Reoviridae . The results of cryo-electron microscopy showed that the BmCPV capsid consists of 60 asymmetric units, and each asymmetric unit contains one turret protein (TP), two large protrusion proteins (LPP) and two capsid shell proteins (CSP). CSP has the ability to self-assemble into virus-like particles (VLPs), and the small protrusion domain (SPD) in CSP may play an essential role in the assembly of viral capsids. In this study, three critical amino acid sites, D828, S829 and V945, in the SPD were efficiently mutated (point mutation) based on the principle of PCR circular mutagenesis. Moreover, a multi-gene expression system, Ac-MultiBac baculovirus, was used to produce eight different recombinant VLPs in vitro . Transmission electron microscopy showed that the single site and double site mutations had little effect on the efficiency and morphology of the assembly of VLPs. Still, the simultaneous mutation of the three sites had a significant impact. The experimental results demonstrate that the SPD of CSP plays an essential role in assembly of the viral capsid, which lays the foundation for further analysis of the molecular and structural mechanism of BmCPV capsid assembly.